AN ANALYSIS OF STUDENTS' ABILITY IN CONSTRUCTING CONDITIONAL SENTENCES (AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 WARINGINKURUNG) - Faisal, Khusnul Khotimah; Amalia, Ila; Suaidi, Afif (Department of Master of Linguistic, Universitas Airlangga, 2023)
Today, many students struggle to construct proper English sentences, particularly in conditional sentences. The teaching methods teachers used failed to engage students. Also, some experts believe that the difficulties students face with conditionals arise from the interaction between meaning and form. So, understanding this relationship and how it frequently appears in conditional sentences is crucial. To address this issue, a study was conducted to assess the proficiency of eleventh-grade students at SMA Negeri 1 Waringinkurung in constructing conditional sentences. The research involved 32 students, and the methodology used was qualitative content analysis, which included tests and interviews. The students' sentences were coded and sorted using a method called summative content analysis. This method involves identifying and measuring specific words or material in the text to understand how they are used. The researcher used various categories like formula of conditional sentences, main and if clauses, modal verbs, verb tense, and word order for further analysis. This analysis helped the researcher evaluate the students' understanding and proficiency in constructing conditional sentences.The study found that students commonly made mistakes in verb tenses and the use of modal verbs. Interviews with the students also confirmed that verb tenses were the most challenging aspect for them. Overall, the research results showd that the students had a good ability to construct conditional sentences, with an average score of 71.75. The findings pinpointed specific areas where students encountered challenges, providing valuable insights for educators to effectively address these issues and enhance overall proficiency.